HEALTH-RELATED QUALITY OF LIFE AND SOCIAL PARTICIPATION OF RESIDENTS IN SHELTERED HOUSING. (11th November 2018) - Balash, L; Sköldunger, A; Sjögren, K; Lövheim, H; Edvardsson, D
Abstract: Sheltered housing is a housing model designed for older people, which in Sweden entails providing older people accessible apartments with elevated opportunities for social participation. Increased social participation is expected to support health and independence, and reduce the need for care and services. Despite the increasing popularity of sheltered housing in Sweden, there are currently no studies on the resident population, their care needs, or levels of social participation. The aim of this study was to examine the health-related quality of life and social participation levels among residents in sheltered housing, compared to aging in place. The method used for this study was a cross sectional survey of older people living in sheltered housing and aging in place in Sweden (n=3805). Descriptive statistics, frequencies, independent t-tests, p-values and effect size were calculated to explore differences between groups. Analyses showed that older people in sheltered housing, compared to aging in place, more frequently reported problems with mobility (64.9%/52, 9%, p=<0.001), self-care (28.2%/19.1%, p=<0.001), usual activities (57.9%/46.7%, p=<0.001), pain/discomfort (84.9%/78.8%, p=<0.001) and anxiety/depression (51.0/39.8%, p=<0.001), as well as lower levels of participation in social activities (57.8%/70.5%, p=<0.001). The results of this study show that the population residing in sheltered housing display lower levels of social participation, and may have more potential care needs than those aging in place, which may explain the choice to move to housing with more perceived support. Time trends, patterns and predictors of social participation require further study in these environments.